Estimation of orbit island width from static magnetic island width, using safety factor and orbit pitch - Shinohara, Kouji; Bierwage, Andreas; Suzuki, Yasuhiro; Kim, Junghee; Matsunaga, Go; Honda, Mitsuru; Rhee, Tongnyeol (Nuclear fusion, 2018)
In order to account for the effect of field perturbations on the transport of fast ions in integrated codes used for the simulation of operational scenarios, it is crucial to develop computationally efficient reduced transport models. Such modeling efforts may greatly benefit from a simple method that determines the width of the island-like structures, which are produced by resonant perturbations in the phase space of the fast ion guiding centers and are known to play a key role for fast ion transport enhancement. In this paper, we present a method for estimating the widths of such 'orbit islands' for passing particles in the presence of static magnetic perturbations. The method consists of mapping the boundaries of magnetic islands from magnetic flux space () into the canonical angular momentum space () of the fast ions. As a working example, we consider co-passing neutral beam (NB) ions subject to a resonant magnetic perturbation (RMP) in a KSTAR tokamak plasma. The estimated orbit island width deviates by less than 25% from the value obtained from Poincaré plots of the actual guiding center trajectories, even when the magnetic drifts are large (here, up to 50% of the minor radius). Our analysis also shows that most of the fast ion transport can be attributed to the effect of isolated islands, which means that stochastization of particle trajectories due to resonance overlaps does not play a major role in the case studied here. The island mapping method proposed here eliminates the need to compute and analyze Poincaré maps of particle trajectories, so that computation times can be reduced tremendously by several orders of magnitude. A further speed-up may be achieved by the development of a method for estimating the width of magnetic islands under realistic conditions.